2022
DOI: 10.36740/wlek202201210
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum Bilirubin Levels in Women With the Antiphospholipid Syndrome

Abstract: The aim: To investigate the relationship between serum bilirubin level and the presence of the APS in women with a history of spontaneous miscarriages. Materials and methods: Fifty six women aged 22-38 (median 27) years with a history of spontaneous miscarriages were divided into two groups: 33 women with the APS and 23 without. Patients were tested for the presence of lupus anticoagulant, anticardiolipin, anti-β2-glycoprotein 1, antiphospholipid antibodies and genetic thrombophilic defects. Results: Groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The available literature suggests that there is an elevation of oxidative stress in SLE, which leads to dysregulation of immune system, abnormal activation and processing of signals related to cell‐death, and production of autoantibodies 3 . According to numberous reports, bilirubin is commonly recognized as an antioxidant and immunomodulator, potentially serving as a safeguard aganist autoimmune disease 4 . It seems related to the disease activity of rheumatoid arthritis, Takayasu arteritis, Crohn's disease, and primary Sjögren's Syndrome 5–7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The available literature suggests that there is an elevation of oxidative stress in SLE, which leads to dysregulation of immune system, abnormal activation and processing of signals related to cell‐death, and production of autoantibodies 3 . According to numberous reports, bilirubin is commonly recognized as an antioxidant and immunomodulator, potentially serving as a safeguard aganist autoimmune disease 4 . It seems related to the disease activity of rheumatoid arthritis, Takayasu arteritis, Crohn's disease, and primary Sjögren's Syndrome 5–7 .…”
Section: Introductionmentioning
confidence: 99%
“…3 According to numberous reports, bilirubin is commonly recognized as an antioxidant and immunomodulator, potentially serving as a safeguard aganist autoimmune disease. 4 It seems related to the disease activity of rheumatoid arthritis, Takayasu arteritis, Crohn's disease, and primary Sjögren's Syndrome. [5][6][7] Besides, many studies have indicated a strong correlation between SLE and serum bilirubin.…”
Section: Introductionmentioning
confidence: 99%